Early Years of Carbapenem-Resistant Enterobacterales Epidemic in Abu Dhabi - Tibor Pál; Aqdas B. Butt; Akela Ghazawi; Jens Thomsen; Tahir A. Rizvi; Ágnes Sonnevend (MDPI AG, 2022)
Recent studies showed that the current endemic of carbapenem-resistant Enterobacterales (CRE) in the Emirate of Abu Dhabi is dominated by highly resistant Klebsiella pneumoniae clones ST14, ST231, and CC147, respectively. In the absence of continuous, molecular typing-based surveillance, it remained unknown whether they lately emerged and rapidly became dominant, or they had been present from the early years of the endemic. Therefore, antibiotic resistance, the presence of carbapenemase and 16S methylase genes, and the sequence types of CRE strains collected between 2009 and 2015 were compared with those collected between 2018 and 2019. It was found that members of these three clones, particularly those of the most prevalent ST14, started dominating already in the very early years of the CRE outbreak. Furthermore, while severely impacting the overall antibiotic resistance patterns, the effect of these clones was not exclusive: for example, increasing trends of colistin or decreasing rates of tigecycline resistance were also observed among nonclonal isolates. The gradually increasing prevalence of few major, currently dominating clones raises the possibility that timely, systematic, molecular typing-based surveillance could have provided tools to public health authorities for an early interference with the escalation of the local CRE epidemic.